A profile of patients attending sports medicine clinics. Issue 4 (1st August 2001) - Finch, C F; Kenihan, M A R
Abstract : Objectives —To describe the sociodemographic profile of sports injury patients who attend sports medicine clinics for treatment and to describe their reasons for choosing to attend such clinics. Method —Data were collected as part of a fully audited injury surveillance system implemented within sports medicine clinics. The study was conducted within five allied multidisciplinary sports medicine clinics in metropolitan Melbourne, Australia. All patients initially presenting for treatment of a new sports or active recreation injury over the period August 1997 to August 1998 were eligible for this study, irrespective of the practitioner providing the treatment. Data were obtained on 6476 patients. Results —The median age of the patients was 25.4 years (range 6.8–81.6) and most were male (69.8% of cases; 95% confidence interval (95% CI) 68.7 to 70.9). Patients had both professional and non-professional backgrounds and were not just local suburb residents. Many patients had insurance cover for their injury treatment: 59.0% (95% CI 58.6 to 59.4) had some private health insurance and 46.6% (95% CI 45.4 to 47.8) had club/association insurance. The most common reasons for attending a clinic was its location (36.8%; 95% CI 36.5 to 37.1) and referral/recommendation (31.0%; 95% CI 30.7 to 31.3). Conclusion —Sports medicine clinics provide treatment for a broad spectrum of injured sports participants across a variety of sporting/recreation contexts. Although these clinics mainly serve the immediate geographic community, the sports speciality and expertise of a particular clinic can attract patients from further afield. This information can help sports medicine clinics to market their services more efficiently to meet the needs of their potential patients.